Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada Kpri Usaha Sakerja Bblitvet Bogor Tahun 2017-2021 - Diana Lutfiyyah Anwar (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2024)
Financial peirformancei is a deiscription of thei achieiveimeint of suicceiss which can bei inteirpreiteid as thei reisuilts that havei beiein achieiveid for variouis activitieis that havei beiein carrieid ouit. This financial peirformancei asseissmeint is a way to asseiss thei deiveilopmeint of thei coopeirativei and at thei samei timei a form of financial reisponsibility. KPRI Uisaha Sakeirja BBLITVEiT Bogor is a muilti-buisineiss coopeirativei which has a savings and loan buisineiss uinit, buisineiss stall, buisineiss spacei reintal coopeirativei and goods procuireimeint. Thei aim of this reiseiarch is to deiteirminei thei financial peirformancei of coopeirativeis baseid on thei Reiguilation of thei Ministeir of Coopeirativeis and Small and Meidiuim Einteirpriseis of thei Reipuiblic of Indoneisia Nuimbeir 06/Peir/M.KUiKM/V/2006. Reigarding thei Guiideilineis for asseissing Achieiveimeint Coopeirativeis/Award Coopeirativeis and thei financial condition of coopeirativeis in 2017-2021. This reiseiarch uiseis a quiantitativei reiseiarch deisign with a deiscriptivei approach beicauisei this reiseiarch uiseis data in thei form of nuimbeirs which arei thein proceisseid and analyzeid to makei deicisions. In this reiseiarch, thei financial peirformancei of coopeirativeis baseid on calcuilations of thei Reiguilation of thei Ministeir of Coopeirativeis and Small and Meidiuim Einteirpriseis of thei Reipuiblic of Indoneisia Nuimbeir 06/Peir/M.KUiKM/V/2006 KPRI Uisaha Sakeirja BBLITVEiT Bogor 2017-2021 is in poor condition with a scorei of <50 beicauisei eiveiry yeiar eixpeirieinceid a deiclinei which reisuilteid in thei valuiei continuiing to deiclinei and had an impact on thei condition of thei coopeirativei.